Developing Formative Assessment Using Quizizz for Assessing English Competence - Abdatul Maazah; Nurul Afidah; Yuyun Bahtiar; Ulfa Wulan Agustina (SCHOOLAR: Social and Literature Study in Education, 2025)
The research aimed to develop a formative assessment using Quizizz to assess English reading skills. The researcher used descriptive text as material and the questions that were created were 50 in multiple-choice types assessment. The subjects of this study were 17 students of the first grade of SMK Pendidikan Megaluh. The research method was the Research and Development (R&D) method that adopted the ADDIE model that consisted of five procedures:  Analysis, Design, Development, Implementation, and Evaluation. From those steps, this research was validated by 4 experts, 2 media experts, and 2 media experts (expert validation). As follows: 1). The results of media validation were 4,5 (better category), 2). The result of material validation was 4,4 (better category), The research got data after implementation as follows: 1). The result of the validity test is invalid, 2). The result of the reliability test used Kuder-Richardson /KR-20 was 0,547 (medium reliability), 3). The result of the difficulty test was 4 in the middle category and 21 in the easier category, 4). The result of the discriminating power test was 1 in the lower category, 12 in the low category, 9 moderate category, and 3 in the good category. 5). The student’s response questionnaire was 86% (better category). Based on the research, the researcher concluded that Quizizz deserved to be used as an assessment instrument because the product was interesting and the student’s response was enthusiastic. Some things that need to be highlighted are the need for revision of the test.